Linking Composite Scores: Effects of Anchor Test Length and Content Representativeness. Issue 2 (20th December 2016) - Lin, Peng; Dorans, Neil; Weeks, Jonathan
Abstract: The nonequivalent groups with anchor test (NEAT) design is frequently used in test score equating or linking. One important assumption of the NEAT design is that the anchor test is a miniversion of the 2 tests to be equated/linked. When the content of the 2 tests is different, it is not possible for the anchor test to be adequately representative of both tests. Lin and Dorans conducted a simulation study in 2010 to investigate the effect of content representativeness of the anchor test on linking via different linking methods when the 2 tests are nonparallel in content structure in the unique case where the groups are equivalent. The current study extends the Lin and Dorans study to the case with nonequivalent group data. Specifically, the current study investigates the impact of content representativeness and length of anchor test on linking when the 2 tests are multidimensional and nonparallel in content structure. The NEAT design was employed. The linking results from 3 classic linear equating methods—Levine observed score, Tucker equating, and chained linear—were examined. The results from the study indicated that equating the tests with different structure should be avoided. For equatings with anchor test, additional bias is likely to be introduced by using an inadequate anchor test. Abstract : Report Number: ETS RR‐16–36